Evaluation of supply chain business process improvements using simulation. (31st August 2005) - Jain, Sanjay; Ervin, Eric
The performance of a supply chain may be improved by implementing e-business concepts across the number of business processes that interact to execute the flow of material and the associated financial transactions. This paper describes an effort utilising modelling and simulation for evaluating the improvements in business processes and systems including a move towards e-business for a logistics and distribution supply chain. The model was abstracted in a manner to put the focus on the business processes while the material flow processes were included at a high level. Model results provided quantification of benefits from different business process improvements. A number of insights applicable to supply chain management are drawn from the results of the analyses.